An analysis of the good faith bargaining practice in the trade union recognition process: reform of the Malaysian trade union legal framework - Abd Razak, Siti Suraya Abd Razak; Nik Mahmod, Nik Ahmad Kamal (IIUM Press, International Islamic University Malaysia, 2019)
The trade union recognition process is a pre-requisite to the collective bargaining action of a trade union. The recognition is important to ascertain the competency of a trade union and the acceptance by the workers to represent them in the collective bargaining action with the employer. However, the ambiguities in the existing legislations on the trade union recognition process in Malaysia and the anti-union practices of the employer are currently depriving the workers of their rights to negotiate for better working conditions. The primary focus of the present work is to identify the weaknesses of the recognition legal framework and the anti-union practices of employers in the recognition process of trade unions. Secondly, is to critically analyse the good faith bargaining practice in other countries and its significance to the recognition process in Malaysia. To explore the anti-union tactics perpetrated by employers, semi-structured interviews have been conducted to analyse the trade unions’ experience in their recognition claims. This research employed a qualitative approach as the instrument to study the good faith bargaining practicesinthe Australian and New Zealand labour law framework. The findings reveal that the good faith bargaining practicesinAustralia and New Zealand have improved the oddsfortrade unions to represent the workers in negotiating collective agreements. The study finally concludes that in order to reform the recognition process of trade unions in Malaysia, the good faith bargaining practice should be implemented in the nation’sindustrial relations law framework.